RESEARCH STUDENTS’ REST FEATURES - Svatenkov, Olexander V. (Educological discourse, 2014)
Leading Ukrainian and foreign researchers one of the causes of deviant behavior of children and young people determine disorganization, the hollowness of their free time. That is why the improvement of preventive work is impossible without reliable data on the leading types and forms of rest of new generation. The article deals with the results of studies of students recreational areas inNizhyn. The most popular restactivities of students is listening to music, watching movies, and social networking. Given in the article the results of research can be used to improve prevention programs, developing social advertising, development pathways socially significant information, etc.